Human rights as a basis for justice in the European Union - Douglas-Scott, Sionaidh (Discussion Papers / Wissenschaftszentrum Berlin für Sozialforschung, WZB Rule of Law Center, 2015)
Justice is a contested concept. A more graspable version of it, it is argued in this paper, is an understanding of it in the context of what is deemed as "injustice" rather than justice. As such, the paper takes a markedly different approach than the perspectives which have emerged so far. A main theme of this paper is the disjunction between, on the one hand, strong reactions to injustice, and a desire for some affective dimension to the EU, some normative adhesive that might bind the EU as an ethical entity; and on the other, the very great difficulty in identifying an enforceable concept of justice in an EU that continues to be driven by a market mentality. There will always remain a gap between the aspiration for justice and its achievement. While the notion of an EU that does not aspire to justice is unthinkable, and EU law must at least hold out a prospect of justice, the gap between aspiration and achievement remains huge. However, this paper also argues that it is the very